Quality of sleep after COVID-19 infection: a cross-sectional study in the Southern Italy - Sansone, Vincenza; Angelillo, Silvia; Paduano, Giovanna; Pileggi, Claudia; Nobile, Carmelo Giuseppe Angelo; Di Giuseppe, Gabriella (Frontiers in Psychiatry, 2024)
This study investigated the quality of sleep in a sample of people from Southern Italy after the major waves of the COVID-19 pandemic, with the aim of evaluating how sleep patterns changed.A cross-sectional study was conducted between March 2022 and January 2023 and involved adults who had COVID-19 infection, invited to complete a self-administered online questionnaire.Results: A total of 408 individuals participated in the survey. Overall, 66.4% had a reduction in social relations and 72.1% had an increase in the use of social media, 86%, 77.2%, and 71.1% reported an extremely severe level of anxiety, stress, and depression, respectively. Almost all of the respondents have had a Pittsburgh Sleep Quality Index score (PSQI) ≥5, indicating poor sleep quality. People with severe or extremely severe depression score, with severe or extremely severe stress score, who had a job and who had experienced someone close who died because of COVID-19 infection, and who had a job were more likely to have a high PSQI global score. The use of sleep medication in the past months was significantly higher in those who were older had higher average age, those who had a job, those who had COVID-19 infection in the first and second waves, those who had someone close who died of COVID-19, and those who did not have changes in the social relationships during the pandemic. Moreover, the participants with severe or extremely severe depression score, with severe or extremely severe stress score, who were females, and who were older had a higher average age have had troubles staying awake while engaging in social activities during the past month.The results bring to light the high prevalence of poor sleep quality among individuals who goet infected by SARS-CoV2 COVID-19 infected. Future research is needed to understand whether how these disorders are still present prolonging even in the present endemic period and whether it is necessary to investigate further determinants that have affected and/or are affecting sleep quality.